Lasmiditan inhibits calcitonin gene-related peptide release in the rodent trigeminovascular system - Labastida-Ramírez, Alejandro (Pain, 2020)
Migraine headache pathophysiology involves trigeminovascular system activation, calcitonin gene-related peptide (CGRP) release, and dysfunctional nociceptive transmission. Triptans are 5-HT(1B/1D/(1F)) receptor agonists that prejunctionally inhibit trigeminal CGRP release, but their vasoconstrictor properties limit their use in migraine patients with cardiovascular disease. By contrast, lasmiditan is a novel antimigraine and selective 5-HT(1F) receptor agonist devoid of vasoconstrictor properties. On this basis, this study has investigated the modulation of trigeminal CGRP release by lasmiditan. For this purpose, we have comparatively analysed the inhibition of several components of the trigeminovascular system induced by lasmiditan and sumatriptan through: ex vivo KCl-induced CGRP release from isolated dura mater, trigeminal ganglion, and trigeminal nucleus caudalis of mice; and in vivo dural vasodilation in the rat closed-cranial window model induced by endogenous (electrical stimulation and capsaicin) and exogenous CGRP. The ex vivo release of CGRP was similarly inhibited by sumatriptan and lasmiditan in all trigeminovascular system components. In vivo, intravenous (i.v.) lasmiditan or higher doses of sumatriptan significantly attenuated the vasodilatory responses to endogenous CGRP release, but not exogenous CGRP effects. These data suggest that lasmiditan prejunctionally inhibits CGRP release in peripheral and central trigeminal nerve terminals. Because lasmiditan is a lipophilic drug that crosses the blood–brain barrier, additional central sites of action remain to be determined.